DOI: 10.17760/d20351619
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perspectives and understanding of social emotional learning in an early elementary suburban public school

Abstract: This study seeks to understand the experiences of early elementary public-school teachers in regard to social emotional learning within their classrooms, which is important because teacher perspectives are rarely accounted for when districts discuss and use social and emotional learning practices. Research is largely focused on student outcomes, but literature shows that teacher outcomes impacts student outcomes and teacher perceptions of social emotional learning can impact their abilities to effectively impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…First, almost half of our teachers (45.4%) stated that including SEL education in language classrooms helps students achieve their academic goals. Numerous previous studies can also be found in the literature, highlighting the tremendous significance of SEL implementation on academic outcomes (Youngblood, 2015;Calkins, 2019;Forrester, 2020).…”
Section: Discussion Of Qualitative Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…First, almost half of our teachers (45.4%) stated that including SEL education in language classrooms helps students achieve their academic goals. Numerous previous studies can also be found in the literature, highlighting the tremendous significance of SEL implementation on academic outcomes (Youngblood, 2015;Calkins, 2019;Forrester, 2020).…”
Section: Discussion Of Qualitative Findingsmentioning
confidence: 98%
“…The participants in prior studies, on the other hand, mentioned several significant obstacles that prevented the incorporation of SEL programs, including minimum length of time, large class size, intense curriculum, insufficient professional SEL training, a lack of self-efficacy, inadequate administrative support, lack of conducive school environment, unavailability of appropriate resources and instructional materials, extensive workload, lack of parental support and an intense focus on cognitive and academic outcomes, all of which served as significant barriers to their attempts to make adjustments in their current teaching methods to conform to the requirements of SEL standards and programs (Aygün & Taşkın, 2017;Rakap et al, 2018;Forrester, 2020).…”
Section: Related Studies About Social and Emotional Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…more than 1 in 50) with looked-after status. Carmarthenshire, in contrast, has 40 and its rates are consistently low, despite a rising trend at a national level (Forrester et al , 2020). Whilst the variation in rates within Wales does correlate with deprivation to an extent, the considerable variation between areas suggests variation in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Forrester (2023) examines teachers' perspectives and understanding of social-emotional learning in an early elementary suburban public school, shedding light on the impact of fidelity in implementation and proper training on the long-term benefits of social-emotional learning programs (Forrester, 2023). This study underscores the importance of fidelity in implementing social-emotional learning programs to maximize their impact on students' well-being.…”
Section: Technology and Digital Learningmentioning
confidence: 99%